STUDY OF THE CHEMICAL COMPOSITION OF JERUSALEM TOPINAMBUR LEAVES AND ROOTS UNDER THE INFLUENCE OF PLANT GROWTH REGULATORS EPIN AND ENERGY-M - Дилшодова Умида Дилшод кизи; Руководитель: Рахматуллина Светлана Рифовна (Innovate Conferences, 2025)
This article presents the results of a study examining the effects of modern growth regulators—Epin (based on epibrassinolide) and Energiya-M (an organosilicon stimulator)—on the biochemical parameters of Jerusalem artichoke (Helianthus tuberosus L.). It was found that the use of these products promotes a significant accumulation of biologically active substances: inulin in tubers, as well as chlorophylls, carotenoids, and ascorbic acid in leaves. Comparative data on the macro- and microelement content depending on the treatment type are provided.
Keywords: Jerusalem artichoke, growth regulators, Epin, Energiya-M, inulin, chemical composition, antioxidants, photosynthetic pigments.